CBCT Radiological Features as Predictors of Nerve Injuries in Third Molar Extractions: Multicenter Prospective Study on a Northeastern Italian Population - Stefano Bigagnoli; Christian Greco; Fulvia Costantinides; Davide Porrelli; Lorenzo Bevilacqua; Michele Maglione (MDPI AG, 2021)
Background: Neurological alterations are one of the main complications occurring after the third molar extractions. The aim of this prospective multicenter cohort study was to find out Cone Beam Computed Tomography (CBCT) features and distribution of neurological complications in patients undergoing lower third molar surgery and to determine the radiological and patient-related factors that could be correlated to the occurrence of inferior alveolar and lingual nerves injury. Material and Methods: 378 patients who underwent lower third molar extraction from March 2018 to March 2019 were included. Clinical and radiological data were collected. CBCT features were recorded following Maglione et al. classification. Symptoms and characteristics of patients who experienced neurological alterations were evaluated. Results: 193 patients needed a second-level radiological exam (CBCT). In these patients, the most common feature was Maglione class 3: a higher frequency of apical or buccal mandibular canals in direct contact with the tooth was observed. 3.17% of the patients developed a neurological complication. Maglione class 4, increased age, and operative time were all positively correlated with neurological alterations. Conclusions: while the buccal or apical position of the mandibular canal was the more common findings, the lingual position was found to have a higher correlation with a negative outcome. Age and operative time were also found to be risk factors for developing nerve injury in the considered population.